LINGUISTIC ANALYSIS OF THE CONTENT OF THE CONCEPT "MAN" (Scientific journal of the Fergana State University, 2023)
The article reflects on the cognitive analysis of the concept of "Man", which is considered a carrier of language and one of the complex concepts. Uzbek linguistics mentions that human categories are not fully characterized and their cognitive semantics are not analyzed.